Perbandingan ketatanegaraan indonesia dan saint kitts & nevis dari berbagai aspek - Saputri, Mahera Yogi (Maliki Interdisciplinary Journal, 2025)
In today’s global era, marked by complex governmental systems and legal dynamics, comparative constitutional studies are essential for understanding how countries design governance structures tailored to their national characteristics and needs. Indonesia and Saint Kitts & Nevis represent two countries with vastly different historical backgrounds, cultures, and political systems. Indonesia adopts a civil law system within a unitary state framework and a presidential form of government, while Saint Kitts & Nevis applies a common law system under a federal structure and a parliamentary government within a constitutional monarchy. This article explores six key aspects: legal system, form of the state, form of government, system of government, constitution, and legislative structure. The study reveals that although both countries uphold the values of democracy and constitutional supremacy, the fundamental differences in their state design reflect their responses to geographical, demographic, and historical conditions. Indonesia emphasizes national integration within a centralized structure, while Saint Kitts & Nevis provides significant local autonomy, particularly for the island of Nevis. This paper offers a fresh perspective in the field of comparative constitutional law and broadens understanding of the flexibility of governance models on a global scale.